Discrete Multistage Optimization and Hierarchical Market - Bistrickas, V. J.; Šimelienė, N. (Nonlinear Analysis: Modelling and Control, 2006)
New simple form of mixed solutions is described by bilinear continuous optimization processes. It enables investigate an analytic solutions and the connection between discrete and continuous optimization processes. Connection between discrete and continuous processes is stochastic. Discrete optimization processes are used for the control works in levels and groups of the hierarchical market. Equilibrium between local and global levels of works is investigated in hierarchical market.
Keywords: connection between discrete and continuous optimization processes; equilibrium control between local and global levels of the works in hierarchical market